Edukasi Penerapan Penggunaan Teknologi yang Bijak terhadap Perilaku Anak Usia Dini - Sakina Sakina; Neneng Hasanah; Astuti Astuti; Risa Yuliani; Siti Masitohe (Abdimisi, 2020)
Gadget is a technology that has a function to facilitate communication for humans. The use of gadgets in the world of education is very influential, especially in finding information and facilitating the learning process of students. However, advances in gadget technology for the world of education also have a negative impact, which can cause students to be lazy to study and play gadgets more often not on time. Service to the Community Pamulang University conducts one of the outreach activities regarding "Education on the Application of Wise Use of Technology to Early Childhood" to students at MI. Unwanul Huda 2 Depok, considering the low knowledge of students about the functions and benefits as well as positive impacts. and the negative impact of using gadgets. This activity aims to (1) motivate students to be wiser in using gadget technology; (2) Providing students with an understanding of the importance of knowing the functions and benefits as well as the positive and negative impacts of using gadget technology as needed. The method of implementing this activity is the Face-to-face Counseling and Interactive method while still running the health protocol. The results of this activity are expected that students at MI. Unwanul Huda 2 Depok can apply the use of gadget technology wisely as needed so as not to harm themselves and others.